Socialization of Dissemination of Agricultural Product Licenses - Maryati, Sri; Putri Meutia Sari (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2025)
This Community Service (CS) activity aimed to promote the importance of business licensing and legality through the management of Business Identification Numbers (NIB) using the Online Single Submission (OSS) system. Conducted at the P2PAKB Hall of the West Aceh Regency Government, it involved 20 business actors. The program utilized lectures, discussions, and hands-on practice, providing participants with training on NIB registration procedures and insights into its benefits, such as market expansion and legal protection. The results showed that participants successfully understood and applied the NIB registration process while recognizing the importance of business legality. Their active participation in discussions and practical sessions indicated the program’s success. With NIB ownership, business actors are expected to enhance the competitiveness of agricultural products, expand their market reach, and support local agribusiness sustainability. This initiative represents a strategic effort to drive rural economic development through agricultural innovation and improved business legality awareness.